1988
DOI: 10.1021/ac00166a018
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric determination of the second acid dissociation constant of oxine bound to controlled pore glass

Abstract: The lonizable surface-group model Is applied to a sorbent consisting of 5-(phenylazo)-8-hydroxyqulnollne covalently bound to controlled pore glass (CPG-OXINE). Capacity measurements combined with Information from potentlometrlc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…The capacity of the immobilised 8-HQ was determined for Cu and Mn was investigated using nitrogen micro-determination by elemental analysis (Kolstad et al, 1988) and by examining the Cu and Mn metal uptake in static and dynamic mode (Nelms et.al., 1995).…”
Section: Determination Of Exchange Capacitymentioning
confidence: 99%
“…The capacity of the immobilised 8-HQ was determined for Cu and Mn was investigated using nitrogen micro-determination by elemental analysis (Kolstad et al, 1988) and by examining the Cu and Mn metal uptake in static and dynamic mode (Nelms et.al., 1995).…”
Section: Determination Of Exchange Capacitymentioning
confidence: 99%
“…In searching for sorbents that are more selective for the species Mn+ than are sulfonated cation exchangers, we have investigated a commercially available sorbent in which a derivative of 5-(phenylazo)-8-hydroxyquinoline (5-P-OXINE) is immobilized on controlled pore glass (CPG-OXINE). In a previous study the ionizable surface group model was used to describe the acid-base behavior of CPG-OXINE (12). In the present study an extension of this model is used to explain the pH and ionic strength dependence of calcium ion sorption by CPG-OXINE, and, in addition, this sorbent is shown to be selective for Ca2+ in the presence of both its anionic and cationic labile complexes.…”
mentioning
confidence: 89%
“…°CaA (6) in which /k is the "thickness" of the diffuse part of the electrical double layer (22,23). Equation 5 can be combined with eq 2, 3, and 6, as well as with the following additional expressions -"ox^oxine/^i (7) £.27(<*h + £.2') (8) 2+ TCa 7T* (12) where k is a constant (23), Pqxine is moles of bound 5-P-OX-INE per gram of CPG-OXINE, 7Ca and 7Ca are ionic activity coefficients for Ca2+ in bulk solution and at x, respectively, aox is the fraction of bound 5-P-OXINE ionized, and Ki2 is the acid dissociation quotient for the phenolic hydroxyl group on bound 5-P-OXINE, defined in terms of activity of H+ in bulk solution, (12).…”
Section: Theorymentioning
confidence: 99%
“…The use of two-photon transitions in efficient ionization schemes has been discussed earlier (1,9,10) and applied to resonance ionization mass spectrometry of several metallic elements (7). Previous flame studies have demonstrated sensitive detection of molecular species by [1 + 1] resonant photoionization in atmospheric pressure flames (11,12).…”
Section: Literature Citedmentioning
confidence: 99%